Web application development project PRES-on dynamic modelling simulation system - Koh, Chia Heng. (2012)
Dynamic, Intelligent, Collaborative are the latest buzzword of the modern software applications of our generation. Keeping up with programmability, usability and robustness of web applications alongside hardware and architectural advancements have been a major issue of technology in the 21th century.